The Effect of Service Quality and Price on Customer Satisfaction of PT. Alam Jaya Wira Sentosa Padang Sidimpuan - Muhammad Fadly Lubis; Suwarno; Husni Muharram Ritonga (Britain International for Academic Research (BIAR) Publisher, 2022)
Marketing is something that can meet or satisfy the needs of customers through various distribution channels through the products offered. Quality of service and price are among the factors that can influence consumer purchasing decisions. This research aims to find out the influence of service quality and price on customer satisfaction in PT. Alamjaya Wirasentosa Padang Sidimpuan. The hypothesis tested is (1) There is a significant influence on the quality of service on customer satisfaction in PT. Alamjaya Wirasentosa Padang Sidimpuan; (2) There is a significant effect of price on customer satisfaction in PT. Alamjaya Wirasentosa Padang Sidimpuan; and (3) There is a significant influence on the Quality of Service and Price together on Customer Satisfaction at PT. Alamjaya Wirasentosa Padang Sidempuan. This research was conducted with survey methods with a quantitative approach. The results of the study concluded; First, there is the influence of quality of service on customer satisfaction in PT. Alamjaya Wirasentosa Padang Sidimpuan. Second, there is a price influence on customer satisfaction in PT. Alamjaya Wirasentosa Padang Sidimpuan. Third, there is the influence of service quality and price together on customer satisfaction at PT. Alamjaya Wirasentosa Padang Sidimpuan. All three showed that the quality of service and price can contribute to customer satisfaction in PT. Alamjaya Wirasentosa Padang Sidimpuan.